EXPLORATION OF PLANTS WITH THE POTENTIAL OF ANTIHYPERTENSION IN SUKU ANAK DALAM (SAD) SUNGAI KIJANG VILLAGE, SUB-DISTRICT OF RAWAS ULU AS A BOOKLET DEVELOPMENT IN THE COMMUNITY - Andriani, Silva; Susanti, Ivoni; Lestari, Fitria (Faculty of Teacher Training and Education Biology Education Departement, 2023)
This study aims to determine the types of antihypertensive plants, parts of plants used as medicine, and how medicinal plants are processed by Suku Anak Dalam/ the Anak Dalam tribe in Rawas Ulu sub-district, Sungai Kijang village, and to find out the results of the development of an exploration booklet on antihypertensive plants in the Anak Dalam tribe . Kijang River, Rawas Ulu District. The results of the study found 12 plant species from 10 families. The part of the plant that is most widely used as medicine by the community is the leaf (58.85%), while the other plant parts used are the fruit (30.77%), stem (7.69), rhizomes (7.69%). The most widely used method of processing medicinal plants by the Anak Dalam Tribe community in Sungai Kijang Village, Rawas Ulu District, namely boiling (57.14%), grating (28.57%) and eating directly (14.29%). The results of the development of an exploration booklet for potentially antihypertensive plants in Suku Anak Dalam, Sungai Kijang Village, Rawas Ulu District, were carried out by three validators, namely a material expert validator of 85%, a media expert validator of 83%, a language expert validator of 85% and a community readability questionnaire involving a small group of 10 people The community indicated that the booklet that had been developed was appropriate and did not need revision.Keywords: Exploration, Plants, Antihypertension, Booklet